THE ROLE OF DISCOURSE MARKERS AS INDICATORS OF SOCIAL RELATIONS IN ENGLISH AND UZBEK FICTION - Qo’chqarova Yoqutxon (TADQIQOTLAR, 2025)
Abstract:This article examines the sociopragmatic role of discourse markers as indicators  of  social  relations  in  English  and  Uzbek  fictional  discourse.  Discourse markers, including pragmatic particles, connectives, fillers, and formulaic expressions, function  as  essential  tools  for  organizing  discourse,  managing  interaction,  and signaling  interpersonal  relationships  between  characters.  The  study  adopts  a comparative  qualitative  approach  to  analyze  how  discourse  markers  reflect  power relations,  social  distance,  politeness,  solidarity,  and  cultural  norms  within  literary communication. The findings reveal that English fiction tends to employ discourse markers  to  express  individual  stance,  indirectness,  and  conversational  mitigation, whereas Uzbek fiction relies more heavily on culturally embedded markers that encode respect,  hierarchy,  and  collective  identity.  The  article  demonstrates  that  discourse markers  are  not  peripheral  linguistic  elements  but  key  sociopragmatic  resources contributing to character development, narrative coherence, and cultural representation in literary texts.